Digital Transformation Journey: a discussion - Khan, Sohail (2018)
Due to disruptive technology all sectors of the businesses have faced massive change in the last decade or more. There is an evolution in the technology and businesses and industries were the major beneficiary of the disruptive technology. The technological improvement led the way to economic growth globally. The widely usage of Internet and personal computers set the path to the new emerging disruptive technology. Technology can have a far reaching impact is it can transform the business and add value to the operation but with all benefits there will be disruption to each and every function of the business. These disruptive technologies can have far reaching impact across different industries such as manufacturing, retail, finance, education, healthcare and academia.